PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN ILIR TIMUR I KOTA PALEMBANG - Ellen Sumiarni (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
The objective of this research is to observe the impact of work environment and labor discipline to employe performance of Pegawai Kecamatan Ilir Timur I Kota Palembang. There are three hypotheses on this research; first, working environment has positive impact to employee performance; second, labor discipline has positive impact to employee performance; third, work environment and labor discipline simultanceously impact positively to employee performance of Pegawai Kecamatan Ilir Timur I Kota Palembang. The population of this research is 78 employees of Regional Library Board South Sumatera Propince. From inferential statistic analysis, correlation coefficient between working environment and employee performance variable is 0.339, while 0.762 for correlation coefficient between labor discipline variable and employee performance variable ( Y ). Correlation coefficient between work environment variable ( X1 ) and labor discipline ( X2 ) to employee performance is 0.767, which show that there is a positive and strong relation. 0.588 determination coefficients means 58.8 % of X1 and X2 variable form Y variable, result doubling linier regression: Y = 12.045 + 0.308X1 + 1.070X2 + ESatistic hypothesis analysis found that; first, partially hypothesis using t test form counting t value as 2.219 with signification 0.033< 0.05, @ = 0,0; Ho denied, means there is a positive ( real ) relation between working situation and employee performance. Second hypothesis ( partially ) 7.247 with signification 0.000<0.05, @ = 0,0 ; Ho denied, means there is positive ( real ) relation between working satisfaction and employee performance. Third hypothesis ( simultaneously ) using F test form 26.409 with signification 0.000< 0.05, 2 = 0,0; Ho denied and H1 expectable, means there is a positive relation between working situation and satisfaction to employee performance. On other word, empirically prove that employee performance improvement linier with improvement of work environment and labor discipline, partially or simultaneously. Keyword : work environment, labor discipline, employe performance